O lúdico no desenvolvimento infantil: um estudo teórico - Santos, Kathiene Regina dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It is a fact that childhood is a period of play and it is through them that the child meets their interests, express their way to organize, disorganize, build, think, making new discoveries. Therefore, the playful stands as one of the most important and effective in children's learning process forms, as it enables the development of imagination, feelings and fantasies, helping the child progress in their motor, psychomotor, cognitive, and physical skills emotional. This gives her the exercise of attention and memory to play activities adults engage, thus expanding their knowledge about the world. The teacher's role in this process is essential, where it can bring to everyday life of the child in various situations themes, turning the simple play on continuous learning and not just using the play as a complementary activity to the child because they provide pleasure and relaxation which do interact with the new learning and the group operates. The psychology emphasizes that play is essential to the balanced development of the psychosocial human being, because when in childhood, the relationship with the toy and gaming in general develops affectivity, creativity, and reasoning ability. Playing, the child increases their independence by building their knowledge. The aim of this work is to make a theoretical study based on a literature search, aiming to understand the play within the child development process, where it is recognized as very important in a child's learning starting from the theoretical conceptions of thinkers such as Piaget, Vygotsky, Wallon among others. With this, it can also be possible to recover the importance of the play that is being extracted from the infant universe due to new reasons to experience the modern world brings, as the excess number of activities assigned to the child, electronic games, etc. Finally, a playful approach to provide a reflection for parents and educators, bringing children's learning...

É fato que a infância é o período de brincadeiras e é por meio delas que a criança satisfaz seus interesses, expressa sua maneira de organizar, desorganizar, construir, pensar, fazendo novas descobertas. Por isso, o lúdico se destaca como uma das formas mais importantes e eficazes no processo de aprendizagem infantil, uma vez que possibilita o desenvolvimento da imaginação, sentimentos e fantasias, ajudando a criança no progresso de suas habilidades motoras, psicomotoras, cognitivas, físicas e emocionais. Isso proporciona a ela o exercício da atenção e memória para reproduzir atividades que os adultos praticam, ampliando assim seu conhecimento sobre o mundo. O papel do professor nesse processo é essencial, onde este pode trazer ao cotidiano da criança situações variadas em temas, transformando o simples brincar em aprendizado contínuo e não utilizando as brincadeiras apenas como uma atividade complementar, pois para a criança, elas proporcionam prazer e descontração, que a fazem interagir com novas aprendizagens e com o grupo no qual está inserida. A psicologia enfatiza que o brincar é fundamental para o desenvolvimento psicossocial equilibrado do ser humano, pois quando na infância, a relação com o brinquedo e jogos em geral desenvolve a afetividade, a criatividade e a capacidade de raciocínio. Brincando, a criança aumenta sua independência, construindo seus conhecimentos. O objetivo do presente trabalho é fazer um estudo teórico a partir de uma pesquisa bibliográfica, visando compreender o lúdico dentro do processo de desenvolvimento infantil, onde este é reconhecido com extrema importância na aprendizagem da criança partindo das concepções teóricas de pensadores como Piaget, Vygotsky, Wallon entre outros. Com isso, pode ser possível também resgatar a importância do brincar que está sendo extraída do universo infantil devido às novas razões que a vivência no mundo moderno traz, como o excesso...
Keywords: Educação pre-escolar; Crianças - Desenvolvimento; Brincadeiras; Psicologia da aprendizagem; Pratica de ensino